Peran CD44 pada Progresivitas Non Alcoholic Steatohepatitis (NASH) - Sarwanti; Marini Stephanie; Ria Kodariah (Majalah Patologi Indonesia, 2020)
Non alcoholic Steatohepatitis (NASH) is part of a group of conditions called Non-Alcoholic Fatty Liver Diseases(NAFLD) where it is a chronic disease, which defined after elimination other causes of fatty liver, such as excessivealcohol consumption and other causes of chronic liver diseases. NASH is fatty liver disease which characterized byballooning of hepatocyte and lobular inflammation with or without fibrosis. Histopathology diagnose on NASH can bedefined by performing liver biopsy. The purpose of liver biopsy is to define level and degree of the disease. Cluster ofDifferentiation (CD) 44 is a transmembrane glycoprotein receptor which located on the surface of macrophage cells,lymphocytes and endothelial cells. In studies which conducted on mice and humans, showed that CD44 playsimportant role in the progression of NASH. CD44 regulates inflammation of adipose tissue and liver. CD44 ispresumed as a marker which increase macrophage infiltration and other inflammatory cells on liver. This processleads to ultimate increment on insulin resistance and fatty liver. Deficiency was discovered on mice which injectedwith methionine and choline deficiency diet (MCDD). CD44 is associated with preventive method to prevent livercomplication by reducing macrophage or monocyte and as well as neutrophil accumulation in liver which wasevaluated through reducing numbers of inflammatory focus, expression of inflammatory cytokines: tumor necrosisfactor Î± (TNFÎ±), interleukin (IL) -1B and nitric oxide synthesis (iNOS), and pro-inflammatory types of macrophage. Inobese patients, number of CD44 is predicted to be increasing.